Analysis of Effective Strategies in Language Teaching for Students at MI Pulutan Salatiga - Indriyatno, Muhamad Agus; Umami, Mashlihatul; Nugroho, Imam Wahyu; Hidayat, Wildan Nur (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to analyze effective language teaching strategies for students at MI Pulutan Salatiga, focusing on methods that enhance student engagement and learning outcomes. A descriptive qualitative approach was used to understand the application of different teaching methods, with data collected through interviews, observations, and document analysis. The findings show that interactive teaching methods such as group discussions and role-playing are more effective than conventional methods, such as lectures and memorization, in increasing student participation and comprehension. Challenges faced in implementing interactive methods include limited facilities, teacher skills in classroom management, and differences in students' learning abilities. Students' responses to interactive methods were very positive; they felt more motivated and confident in using the language in contextual settings. Based on these findings, it is recommended that MI Pulutan increase support for the use of more varied methods and provide training for teachers to optimize the learning process. Creative and interactive teaching strategies have been proven to have a significant impact on the development of students' language skills, which is crucial in supporting their academic achievements and communication abilities in the future.